The Palgrave Handbook of the International Political Economy of Energy - Van de Graaf, Thijs; Sovacool, Benjamin K.; Ghosh, Arunabha; Kern, Florian; Klare, Michael T.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This Handbook is the first volume to analyse the International Political Economy, the who-gets-what-when-and-how, of global energy. Divided into five sections, it features 28 contributions that deal with energy institutions, trade, transitions, conflict and justice. The chapters span a wide range of energy technologies and markets - including oil and gas, biofuels, carbon capture and storage, nuclear, and electricity - and it cuts across the domestic-international divide. Long-standing issues in the IPE of energy such as the role of OPEC and the 'resource curse' are combined with emerging issues such as fossil fuel subsidies and carbon markets. IPE perspectives are interwoven with insights from studies on governance, transitions, security, and political ecology. The Handbook serves as a potent reminder that energy systems are as inherently political and economic as they are technical or technological, and demonstrates that the field of IPE has much to offer to studies of the changing world of energy.
Part I. Introduction -- Chapter 1: States, markets and institutions: Integrating International Political Economy and global energy politics; Thijs Van de Graaf, Benjamin K. Sovacool, Arunabha Ghosh, Florian Kern, and Michael T. Klare -- Part II: Energy actors and institutions; Primary editor: Thijs Van de Graaf -- Chapter 2: Actors, frames and institutions in global energy politics; Thijs Van de Graaf and Fariborz Zelli -- Chapter 3: The past, present and future role of OPEC; Bassam Fattouh and Anupama Sen -- Chapter 4: Corporations, civil society and disclosure: a case study of the Extractive Industries Transparency Initiative (EITI); James van Alstine and Nathan Andrews -- Chapter 5: The UN, energy, and the Sustainable Development Goals; Sylvia Karlsson-Vinkhuyzen -- Chapter 6: The World Trade Organization's role in global energy governance; Timothy Meyer -- Part III: Energy trade, finance and investment; iv>Primary editor: Arunabha Ghosh -- Chapter 7: Green energy trade conflicts: the political economy of a future energy system; Arunabha Ghosh; Chapter 8: The Transatlantic Trade and Investment Partnership, energy and divestment; Rafael Leal-Arcas and Constantino Grasso -- Chapter 9: The international oil and gas pricing regimes; Ustina Markus -- Chapter 10: The political economy of carbon markets; Richard Lane and Peter Newell -- Chapter 11: The politics and governance of energy subsidies; Harro van Asselt and Jakob Skovgaard -- PART IV. Energy transitions; Primary editor: Florian Kern -- Chapter 12: Energy transition studies and political economy considerations: prospects and challenges; Florian Kern and Jochen Markard -- Chapter 13: Developing and Deploying Carbon Capture and Storage Technologies: Explaining uneven progress; James Meadowcroft and James Gaede -- Chapter 14: Democracy and transitions: European experiences of policy inclusiveness and changes in the electricity industry; Mari Ratinen and Peter D. Lund -- Chapter 15: Second life or half-life? The contested future of nuclear power and its potential role in a sustainable energy transition; M.V. Ramana -- Chapter 16: The politics of biofuels -- John Alic; Part V. Energy conflict and the resource curse; Primary editor: Michael T. Klare -- Chapter 17: No blood for oil? Hydrocarbon abundance and international security; Michael T. Klare -- Chapter 18: Do countries fight over oil? Emily Meierding -- Chapter 19: Does Russia have a potent gas weapon? James Henderson -- Chapter 20: Energy, coercive diplomacy and sanctions Llewellyn Hughes and Eugene Gholz -- Chapter 21: The resource curse puzzle across four waves of research; William Gochberg and Victor Menaldo -- Part VI: Energy justice and political ecology; Primary editor: Benjamin K. Sovacool -- Chapter 22: The political ecology and justice of energy; Benjamin K. Sovacool -- Chapter 23: The political ecology of oil and gas in West Africa's Gulf of Guinea: State, petroleum, and conflict in Nigeria; Michael J. Watts -- Chapter 24: Dispossession, justice and a sustainable energy future; Majia H. Nadesan and Martin Pasqualetti -- Chapter 25: Energy and global production networks; Dustin Mulvaney -- Chapter 26: Enclosure and exclusion within emerging forms of energy resource extraction: shale fuels and biofuels; Arielle Hesse, Jennifer Baka, and Kirby Calvert -- Chapter 27: The political economy of energy justice: A nuclear energy perspective; Kirsten Jenkins, Raphael Heffron, and Darren McCauley -- Chapter 28: Energy justice in theory and practice: Building a pragmatic roadmap; Mark Cooper.-.
Keywords: Political economy